2011
DOI: 10.4236/me.2011.25100
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Listed Companies’ Earnings Quality and Internal Control Information Disclosure

Abstract: This article examines the relationship of earnings quality and internal control disclosure information in the sample of 1273 nonfinancial firms in shanghai and Shenzhen Stock Exchange in 2010. Using multiple regression model, we launch an empirical analysis on the relationship between earnings quality and internal control disclosure information. We find a positive relation between earnings quality and internal control disclosure information. The better the earnings quality is, the higher level of the internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…However, internal control is defined as a process, affected by the actions of board of directors and other organizational structure levels in the firm, designed to provide reasonable assurance toward achieving firm's objectives, plans and strategies under the related laws, rules, polices and regulations (Domnişoru & Vînătoru, 2008;Li & Wei, 2008). Recently, big companies increasingly started to include detailed management reports on the effectiveness and efficiency of internal control systems in their annual corporate reports as an indicator to a good corporate governance practice (Leng & Li, 2011;Saha & Arifuzzaman, 2011). However, the evaluation of internal control system is based mainly on assessment of the internal quality control of the intended company on three main levels, including appropriate internal control, insufficient internal control and deficient internal control (Calotă & Iana, 2009).…”
Section: Internal Control and Audit Program Effectivenessmentioning
confidence: 99%
“…However, internal control is defined as a process, affected by the actions of board of directors and other organizational structure levels in the firm, designed to provide reasonable assurance toward achieving firm's objectives, plans and strategies under the related laws, rules, polices and regulations (Domnişoru & Vînătoru, 2008;Li & Wei, 2008). Recently, big companies increasingly started to include detailed management reports on the effectiveness and efficiency of internal control systems in their annual corporate reports as an indicator to a good corporate governance practice (Leng & Li, 2011;Saha & Arifuzzaman, 2011). However, the evaluation of internal control system is based mainly on assessment of the internal quality control of the intended company on three main levels, including appropriate internal control, insufficient internal control and deficient internal control (Calotă & Iana, 2009).…”
Section: Internal Control and Audit Program Effectivenessmentioning
confidence: 99%
“…Profit presented in financial statements can be said to possess a good quality if it has a high level of reliability and trust (Wang et al, 2015). Leng and Li (2011) reveal that reported earnings quality can increase the internal control disclosure systems owned by companies, where companies with good earnings quality tend to reveal higher internal control because the conditions that occur presents the good news for various parties.…”
Section: Earnings Quality and Internal Control Disclosurementioning
confidence: 99%
“…Audit committee members who have expertise in finance and accounting will be able to improve the quality of financial statements (Suprianto et al, 2017). Furthermore, a prior study found that an efficient audit committee characteristics will support an excellent supervisory function to improve the quality of corporate earnings (Gao & Huang, 2016), which shows the implementation of the company's internal controls (Leng & Li, 2011). Some studies revealed the significance of the disclosure of the company's internal controls in ASEAN, which includes Indonesia (Asian Development Bank, 2014;Billet et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Internal control, however, is defined as a process, influenced by the actions of the board of directors and other levels of organizational structure within an entity, and is designed to ensure reasonable attainment of corporate goals, plans and strategies in accordance with the laws, relevant policies and regulations. Recently, large firms have begun to include detailed management reports on the effectiveness of internal controls in the annual reports as an indicator for a good corporate governance practice (Leng & Li, 2011;Saha & Arifuzzaman, 2011). The effectiveness of an enterprise's internal control is often considered as a prerequisite for the audit process as it is a key determinant of timing, extent and nature of an audit.…”
Section: Literature Reviewmentioning
confidence: 99%